Examination of basic motor skills in children and adolescents - Karadeniz, Soner; Suveren, Ceren; Arslan, Yasin; Ayyıldız Durhan, Tebessüm; Ceylan, Tülay; Albay, Faruk; Küçük, Hamza; Ceylan, Levent (Frontiers in Physiology, 2024)
In this study, it aims to evaluate the gross motor coordination of girls and boys between the ages of 5-14.The study group of this research consists of a total of 842 children between the ages of 5-14 studying in 10 randomly selected different kindergartens and primary schools in Sivas city center in the 2021-2022 academic year. Of the students participating in the study, 421 (50%) were female and 421 (50%) were male. When the age distribution of the children is examined, 13.3% are 5-6 years old, 29.5% are 7-8 years old, 21.5% are 9-10 years old, 16.4% are 11-12 years old, 19% are 11-12 years old. It was determined that, 4 were between the ages of 13-14. KTK (Körperkoordinationstest für Kinder) test was used to measure motor skills.Findings: When the classification of children according to KTK defining classes is examined, 40.7% are very good, When the children's KTK Backward Balancing scores were examined, a statistically significant difference was found between gender and age groups (p <0.05). While it was determined that girls' KTK backward balancing scores were higher than boys. KTK Total Total scores were examined according to the Body Mass Index groups, a statistically significant difference was determined between the groups for the variables examined (p <0.05). The lowest scores were generally obtained by the children in the obese group.One of the results we found in our study shows that age has a significant effect on the development of basic movement skills. It has been observed that as age increases. there is an increase in KTK General Total scores. . It was determined that girls' KTK backward balancing scores were higher than boys. This result can also be explained by the effect of developmental difference on age. According to BMI, obesity; It is thought that it may negatively affect children's motor skills development and motor performance, and this may cause decreases in motor competence compared 2 This is a provisional file, not the final typeset article to normal weight children. According to this result, it is thought that it is important to diagnose motor disorders in obese children early.